2011
DOI: 10.3899/jrheum.101295
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ro/SSA Antibodies Are an Independent Factor Associated with an Insufficient Response to Tumor Necrosis Factor Inhibitors in Patients with Rheumatoid Arthritis

Abstract: The presence of anti-Ro might be related to the lesser clinical response to infliximab compared to other TNF inhibitors, suggesting that the presence of anti-Ro should be considered when choosing the appropriate biologics for patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Interestingly, a recent study showed that RA patients with secondary SS developed more severe arthritis and higher RA disease activity than those without secondary SS [26]. Another study showed that the presence of anti-SS-A antibody and secondary SS in patients with RA could lower clinical response to TNF inhibitors [27]. The latter study reported that the EULAR responder (good or moderate) rate in RA patients with secondary SS or anti-SS-A antibody was significantly lower (63% in secondary SS and 58% in anti-SS-A antibody-positive patients) than in those without secondary SS or anti-SS-A antibody (82% and 83%, respectively) [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study showed that RA patients with secondary SS developed more severe arthritis and higher RA disease activity than those without secondary SS [26]. Another study showed that the presence of anti-SS-A antibody and secondary SS in patients with RA could lower clinical response to TNF inhibitors [27]. The latter study reported that the EULAR responder (good or moderate) rate in RA patients with secondary SS or anti-SS-A antibody was significantly lower (63% in secondary SS and 58% in anti-SS-A antibody-positive patients) than in those without secondary SS or anti-SS-A antibody (82% and 83%, respectively) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the presence of anti-SS-A antibody and secondary SS in patients with RA could lower clinical response to TNF inhibitors [27]. The latter study reported that the EULAR responder (good or moderate) rate in RA patients with secondary SS or anti-SS-A antibody was significantly lower (63% in secondary SS and 58% in anti-SS-A antibody-positive patients) than in those without secondary SS or anti-SS-A antibody (82% and 83%, respectively) [27]. In the present study, we demonstrated that abatacept was effective even for RA involvement in most (82.9%) patients with RA and secondary SS who were positive for anti-SS-A antibody with a high adherence rate for 52 weeks, though such patients are considered to have severe disease and are often resistant to TNF inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors also have mentioned a strong association between anti-Ro antibodies and the development of side effects by treatment with gold salts or D-penicillamine [144146]. In a recent report anti-Ro antibodies are suggested to be an independent factor associated with an insufficient response to tumor necrosis factor (TNF) inhibitors in patients with RA [147]. …”
Section: Anti-ro Antibodies and Autoimmune Diseasesmentioning
confidence: 99%
“…Anti-SSA/Ro mainly targets the autoantigen Ro52 (41). However, as with many mediators involved in this disease, the precise role of these autoantibodies in the pathogenesis of this condition is not clearly understood.…”
Section: Resultsmentioning
confidence: 99%